The Effect Of Human Resources Development And Work Environment Towards Employee Performance Improvement PDAM Surya Sembada City Of Surabaya - Witta Anggraeni; Hermien Tridayanti; Mohammed Mustafa Hussein Al-Amrani (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2018)
This study aims to analyze the effect of Human Resource Development and Work Environment towards Employee Performance Improvement PDAM Surya Sembada City Of Surabaya (Study of the Corporate Secretary Sub-Directorate) partially and simultaneously. The authors used a saturated sampling technique or also called a census, where all members of the population are sampled, as many as 55 employees in all Sub-Directorate of Corporate Secretary PDAM Surya Sembada City Of Surabaya. Data collection techniques using questionnaires and interview. In calculating scoring, researchers used a Likert scale. Method data analysis used is multiple linear regression analysis. The results of this study show that the variable Human Resource Development (X1) and Work Environment (X2) have a significant effect on Employee Performance Improvement (Y) partially. Human Resource Development (X1) and Environment Variables Work (X2) also have a significant effect on Employee Performance Improvement (Y) simultaneously.